Polyethylene-copper nanoparticle composite material and preparation method and application thereof
By adding Tween modified copper nanoparticles to the support material of the water surface photovoltaic power station, the polyethylene-copper nanoparticle composite material is formed, which solves the problem that high-density polyethylene materials are easily adhesive, and the mechanical properties of the materials are improved and the anti-pollution performance is enhanced.
Patent Information
- Application Number
- CN202310546431.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-05-15
AI Technical Summary
The supporting material of water surface photovoltaic power stations is easily adhered to biologically due to its inherent hydrophobicity and high dirt affinity, resulting in material corrosion and reduced power generation efficiency.
The polyethylene-copper nanoparticle composite material is used to improve the mechanical properties and thermal stability of the material by adding Tween modified copper nanoparticles to the polyethylene material, and inhibit biological adhesion through the antibacterial and anticorrosive effects of the copper nanoparticles.
It effectively inhibits the growth of bacteria and aquatic organisms, extends the service life of the material, improves the anti-pollution performance, and improves the overall performance of polyethylene materials.
Smart Images

Figure CN116622142B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-pollution materials, and in particular to a polyethylene-copper nanoparticle composite material and a preparation method and application thereof. Background Art
[0002] Water surface photovoltaic power station refers to a new type of photovoltaic power station that uses floating bodies to support photovoltaic modules. It can be widely used in coal mining subsidence areas, lakes, reservoirs and other water surface spaces. Water surface photovoltaic power stations do not occupy arable land and are suitable for areas with abundant water resources and scarce land resources. The use of water surface photovoltaic power stations can reduce water evaporation, inhibit algae reproduction, and protect water resources.
[0003] Water surface photovoltaic power stations mostly use special floats made of polyethylene blow molding as supporting materials, such as high-density polyethylene materials. High-density polyethylene has many excellent properties, such as good mechanical strength, good chemical resistance and thermal stability. However, due to its inherent hydrophobicity, non-wetting property, the absence of any active functional groups and high dirt affinity. Therefore, other organisms can easily attach to its surface, increase the weight of the float, and gradually corrode the float, causing the supporting material to fail, affecting the power generation efficiency and power generation cost of the water surface photovoltaic power station.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a polyethylene-copper nanoparticle composite material and a preparation method and application thereof.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a polyethylene-copper nanoparticle composite material, comprising a polyethylene matrix and copper nanoparticles dispersed in the polyethylene matrix, wherein the copper nanoparticles are Tween-modified copper nanoparticles.
[0008] In an alternative embodiment, the polyethylene is high density polyethylene.
[0009] Preferably, the molecular weight of the high-density polyethylene is 3 to 6 million.
[0010] In an alternative embodiment, the weight ratio of the copper nanoparticles to the high-density polyethylene is 0.5-1%.
[0011] Preferably, the particle size of the copper nanoparticles is 10 to 30 nm.
[0012] In an optional embodiment, the average particle size of the Tween-modified copper nanoparticles is 100-110 nm.
[0013] Preferably, the content of Tween is 0.1-1%.
[0014] Preferably, the Tween comprises any one of Tween 20, Tween 40, Tween 60 or Tween 80.
[0015] In an optional embodiment, the diameter of the polyethylene-copper nanoparticle composite monofilament is 0.1-0.3 mm.
[0016] In a second aspect, the present invention provides a method for preparing a polyethylene-copper nanoparticle composite material as described in any of the aforementioned embodiments, comprising melt spinning a mixed solution obtained by mixing a Tween-modified copper nanoparticle suspension with a polyethylene solution.
[0017] In an optional embodiment, the mixing reaction of the Tween-modified copper nanoparticle suspension and the polyethylene solution includes stirring the reaction under heating in a water bath.
[0018] Preferably, the water bath heating temperature is 95-100°C.
[0019] Preferably, the stirring time is 0.5 to 2 hours.
[0020] In an optional embodiment, melt spinning includes placing the mixed solution in a twin-screw extruder for extrusion and then placing it in a single-screw extruder for extrusion to obtain polyethylene-copper nanoparticle composite material monofilaments.
[0021] Preferably, the temperature of the single screw extruder is 250-270° C., and the stretch ratio is 7.0-9.0.
[0022] Preferably, the extrusion temperature of the twin-screw extruder is 200-300°C.
[0023] In an alternative embodiment, the preparation of the Tween-modified copper nanoparticle suspension comprises dispersing the copper nanoparticles into an alcohol solution of Tween and stirring.
[0024] Preferably, the content of Tween in the alcohol solution of Tween is 0.1-1%.
[0025] Preferably, the stirring time is 3 to 10 minutes.
[0026] Preferably, the alcoholic solution of Tween is ethanol.
[0027] In a third aspect, the present invention provides a polyethylene-copper nanoparticle composite material as in any of the aforementioned embodiments or a polyethylene-copper nanoparticle composite material prepared by the preparation method as in any of the aforementioned embodiments in an anti-pollution plastic product.
[0028] The present invention has the following beneficial effects:
[0029] The present invention provides a polyethylene-copper nanoparticle composite material and a preparation method and application thereof. By adding copper nanoparticles to polyethylene materials, on the one hand, the polyethylene materials have a good inhibitory effect on bacteria and can inhibit the growth of aquatic organisms; on the other hand, the copper nanoparticles can improve the mechanical properties and thermal stability of the polyethylene materials, thereby achieving the effect of increasing the service life of the polyethylene materials from a dual perspective. The use of Tween-modified copper nanoparticles can slowly release the copper nanoparticles to exert their good anti-pollution performance, and at the same time, the copper nanoparticles can be evenly dispersed, thereby improving the overall antibacterial, anticorrosive and anti-pollution performance of the polyethylene-copper nanoparticle composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 The infrared spectrum of the copper nanoparticles provided by the present invention;
[0032] Figure 2 The dynamic scattered light results of the copper nanoparticles provided by the present invention;
[0033] Figure 3 This is a scanning electron microscope image of the polyethylene-copper nanoparticle composite material provided in Example 1 of the present invention;
[0034] Figure 4 This is a scanning electron microscope image of the polyethylene-copper nanoparticle composite material provided in Example 2 of the present invention;
[0035] Figure 5 This is a scanning electron microscope image of the polyethylene-copper nanoparticle composite material provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] In a first aspect, the present invention provides a polyethylene-copper nanoparticle composite material, comprising a polyethylene matrix and copper nanoparticles dispersed in the polyethylene matrix, wherein the copper nanoparticles are Tween-modified copper nanoparticles.
[0038] In the current scheme of using copper as anti-fog coating, due to the effect of salt ions in seawater, a large amount of copper will be released after the coating is immersed in seawater, resulting in coating failure. In order to solve this problem, the inventor creatively proposed the use of Tween-modified copper nanoparticles, which can slowly release copper nanoparticles and exert their good anti-pollution performance. At the same time, the copper nanoparticles can be evenly dispersed, improving the overall antibacterial, anti-corrosion and anti-pollution properties of the polyethylene-copper nanoparticle composite material. In addition, on the one hand, it can maintain the inhibitory effect of copper on bacteria and inhibit the growth of aquatic organisms; on the other hand, copper nanoparticles can improve the mechanical properties and thermal stability of polyethylene materials, achieving the effect of improving its service life from a dual angle.
[0039] In an alternative embodiment, the polyethylene is high density polyethylene.
[0040] Preferably, the molecular weight of the high-density polyethylene is 3 to 6 million.
[0041] In an optional embodiment, the weight ratio of the copper nanoparticles to the high-density polyethylene is 0.5-1%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%. The weight ratio of the copper nanoparticles to the high-density polyethylene is controlled within the above range, and the Tween-modified copper nanoparticles obtained in the polyethylene-copper nanoparticle composite material are nearly spherical and have uniform particle size.
[0042] Preferably, the particle size of the copper nanoparticles is 10-30 nm; for example, it may be 10 nm, 15 nm, 20 nm, 25 nm or 30 nm.
[0043] In an optional embodiment, the average particle size of the Tween-modified copper nanoparticles is 100-110 nm; for example, it may be 100 nm, 102 nm, 104 nm, 106 nm, 108 nm or 110 nm.
[0044] Preferably, the content of Tween is 0.1-1%, for example, it may be 0.1%, 0.3%, 0.5%, 0.7%, 0.9% or 1.0%.
[0045] Preferably, Tween includes any one of Tween 20, Tween 40, Tween 60 or Tween 80. As a non-ionic surfactant, Tween has lubricating and cleaning properties, so using Tween to modify copper nanoparticles can improve the hydrophilicity of copper ions.
[0046] In an optional embodiment, the diameter of the polyethylene-copper nanoparticle composite monofilament is 0.1-0.3 mm; for example, it can be 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm or 0.3 mm.
[0047] Preferably, the polyethylene-copper nanoparticle composite material can be a polyethylene-copper nanoparticle composite film, a polyethylene-copper nanoparticle composite tube, a polyethylene-copper nanoparticle composite plate or a product of other shapes made from the polyethylene-copper nanoparticle composite material.
[0048] In a second aspect, the present invention provides a method for preparing a polyethylene-copper nanoparticle composite material as described in any of the aforementioned embodiments, comprising melt spinning a mixed solution obtained by mixing a Tween-modified copper nanoparticle suspension with a polyethylene solution.
[0049] In an optional embodiment, the mixing reaction of the Tween-modified copper nanoparticle suspension and the polyethylene solution includes stirring the reaction under heating in a water bath.
[0050] Preferably, the temperature of the water bath heating is 95-100°C; for example, it may be 95°C, 96°C, 97°C, 98°C, 99°C or 100°C.
[0051] Preferably, the stirring time is 0.5 to 2 h; for example, it can be 0.5 h, 1 h, 1.5 h or 2 h.
[0052] In an optional embodiment, melt spinning includes placing the mixed solution in a twin-screw extruder for extrusion and then placing it in a single-screw extruder for extrusion to obtain polyethylene-copper nanoparticle composite material monofilaments.
[0053] Preferably, the temperature of the single screw extruder is 250-270° C., for example, 250° C., 255° C., 260° C., 265° C. or 270° C. The stretch ratio is 7.0-9.0, for example, 7.0, 7.5, 8.0, 8.5 or 9.0.
[0054] Preferably, the extrusion temperature of the twin-screw extruder is 200-300°C.
[0055] In an alternative embodiment, the preparation of the Tween-modified copper nanoparticle suspension comprises dispersing the copper nanoparticles into an alcohol solution of Tween and stirring.
[0056] Preferably, the content of Tween in the alcohol solution of Tween is 0.1-1%, for example, it may be 0.1%, 0.3%, 0.5%, 0.7%, 0.9% or 1.0%.
[0057] Preferably, the stirring time is 3 to 10 min; for example, it can be 3 min, 5 min, 7 min, 9 min or 10 min.
[0058] Preferably, the alcoholic solution of Tween is ethanol.
[0059] In a third aspect, the present invention provides a polyethylene-copper nanoparticle composite material as in any of the aforementioned embodiments or a polyethylene-copper nanoparticle composite material prepared by the preparation method as in any of the aforementioned embodiments in an anti-pollution plastic product.
[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0061] Example 1
[0062] This embodiment provides a polyethylene-copper nanoparticle composite material, and the preparation method thereof is as follows:
[0063] S01. Disperse copper nanoparticles with a particle size of 20 nm in an ethanol solution containing 0.5% Tween 20, and stir for 5 minutes during the dispersion process to obtain a Tween-modified copper nanoparticle suspension.
[0064] S02, adding the Tween-modified copper nanoparticle suspension obtained in step S01 to the high-density polyethylene solution, shaking for 30 minutes, and then heating and stirring in a water bath at a water bath temperature of 98° C. and stirring for 1 hour, to obtain a mixed solution after the stirring is completed.
[0065] The weight ratio of the copper nanoparticles to the high-density polyethylene is 0.5%.
[0066] S03, extruding the mixed solution obtained in step S02 through a twin-screw extruder, and then feeding the mixed solution into a single-screw extruder for melt spinning to obtain a polyethylene-copper nanoparticle composite material.
[0067] The parameters of the twin-screw extruder are 50 mm screw diameter, aspect ratio of 35, and rotation speed of 1300-1500 rpm.
[0068] The parameters of the single screw extruder are: spinning temperature 240°C, stretch ratio 8.0.
[0069] The diameter of the prepared polyethylene-copper nanoparticle composite monofilament is 0.2 mm.
[0070] Example 2
[0071] This embodiment provides a polyethylene-copper nanoparticle composite material, and the preparation method thereof is as follows:
[0072] S01. Disperse copper nanoparticles with a particle size of 20 nm in an ethanol solution containing 0.5% Tween 20, and stir for 5 minutes during the dispersion process to obtain a Tween-modified copper nanoparticle suspension.
[0073] S02, adding the Tween-modified copper nanoparticle suspension obtained in step S01 to the high-density polyethylene solution, shaking for 30 minutes, and then heating and stirring in a water bath at a water bath temperature of 98° C. and stirring for 1 hour, to obtain a mixed solution after the stirring is completed.
[0074] The weight ratio of the copper nanoparticles to the high-density polyethylene is 1.0%.
[0075] S03, extruding the mixed solution obtained in step S02 through a twin-screw extruder, and then feeding the mixed solution into a single-screw extruder for melt spinning to obtain a polyethylene-copper nanoparticle composite material.
[0076] The parameters of the twin-screw extruder are 50 mm screw diameter, aspect ratio of 35, and rotation speed of 1300-1500 rpm.
[0077] The parameters of the single screw extruder are: spinning temperature 240°C, stretch ratio 8.0.
[0078] The diameter of the prepared polyethylene-copper nanoparticle composite monofilament is 0.2 mm.
[0079] Comparative Example 1
[0080] This comparative example provides a polyethylene-copper nanoparticle composite material, and its preparation method is the same as that of Example 1, except that the weight ratio of copper nanoparticles to high-density polyethylene is 2.0%.
[0081] Comparative Example 2
[0082] This comparative example provides a polyethylene-copper nanoparticle composite material, and its preparation method is the same as that of Example 1, except that the extrusion temperature of the twin-screw extruder is 450°C.
[0083] Comparative Example 3
[0084] This comparative example provides a polyethylene-copper nanoparticle composite material, and its preparation method is the same as that of Example 1, except that: S02, the Tween-modified copper nanoparticle suspension obtained in step S01 is added to the high-density polyethylene solution, shaken for 60 minutes, and then heated in a water bath and stirred. The water bath heating temperature is 70° C., and the stirring time is 1 hour.
[0085] Test example
[0086] 1) Characterization of Tween-modified copper nanoparticles
[0087] The Tween-modified copper nanoparticles and the unmodified nanoparticles prepared in Example 1 were characterized by infrared spectroscopy FT-IR to obtain the following: Figure 1 Results shown.
[0088] Figure 1 A is the infrared characterization curve of the Tween-modified copper nanoparticles prepared in Example 1; B is the infrared characterization curve of the unmodified copper nanoparticles. Figure 1 It can be seen that the Tween-modified copper nanoparticles have a -1 There is an obvious absorption band between 3700-3000cm -1 The broad absorption band is the stretching vibration of hydroxyl (-OH). And the infrared characterization curve of Example 1 obviously migrates to the high wave number direction, indicating that the Tween reagent is adsorbed on the surface of the copper nanoparticles.
[0089] By analyzing the dynamic scattered light results of the Tween-modified copper nanoparticles and the unmodified nanoparticles prepared in Example 1, as shown in FIG. Figure 2 shown.
[0090] Figure 2 A is the dynamic scattered light result of the Tween-modified copper nanoparticles prepared in Example 1; B is the dynamic scattered light result of the unmodified copper nanoparticles. Figure 2 It can be seen that the particle size of the unmodified copper nanoparticles is 20nm. Due to the high surface energy, a large amount of agglomeration is found, and the average particle size after agglomeration is 170nm. The average particle size of the Tween-modified copper nanoparticles is 105nm. It can be clearly seen that the tendency of agglomeration is weakened due to the adsorption of the surfactant.
[0091] 2) Microstructure of polyethylene-copper nanoparticle composites
[0092] The polyethylene-copper nanoparticle composite materials of Examples 1 to 2 and Comparative Example 1 were observed under a scanning electron microscope. Figure 3 to Figure 5 The results are shown. Figure 3 to Figure 5 It can be seen that the morphology of the copper nanoparticles in the polyethylene-copper nanoparticle composites provided in Examples 1 and 2 of the present invention is nearly spherical, and the morphology of the copper nanoparticles in the polyethylene-copper nanoparticle composites provided in Comparative Example 1 presents an irregular non-spherical structure, indicating that in Comparative Example 1, due to the high melt viscosity during melt spinning and the hydrophilic modification between the copper nanoparticles, the Tween-modified copper nanoparticles are not completely dissociated and dispersed.
[0093] 3) Antifouling ability of polyethylene-copper nanoparticle composites
[0094] At 25°C and 1.5 MPa pressure, films made of the polyethylene-copper nanoparticle composite materials of Examples 1 to 2 and Comparative Examples 1 to 3 were tested to test the separation results of different films for 2 g / L NaCl inorganic salt solution, as shown in Table 1.
[0095] Table 1 Anti-pollution ability of different films
[0096]
[0097] As shown in Table 1, the polyethylene-copper nanoparticle composite material and its preparation method and application provided by the embodiment of the present invention have better anti-pollution ability, while the comparative example 1 has poor effect because the copper particle content is too high and does not fully participate in the reaction. The comparative example 2 has poor effect because the extrusion temperature of the twin-screw extruder is too high, resulting in uneven spinning. The comparative example 3 has poor effect because the water bath heating temperature does not reach the critical condition for full reaction.
[0098] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a polyethylene-copper nanoparticle composite material in anti-pollution plastic products, characterized in that: The polyethylene-copper nanoparticle composite material comprises a polyethylene matrix and copper nanoparticles dispersed in the polyethylene matrix, the copper nanoparticles are Tween-modified copper nanoparticles, and the polyethylene is high-density polyethylene; The weight ratio of the copper nanoparticles to the high-density polyethylene is 0.5-1%; The particle size of the copper nanoparticles before Tween modification is 10-30 nm, and the average particle size of the copper nanoparticles modified by Tween is 100-110 nm; The preparation method of the polyethylene-copper nanoparticle composite material comprises the steps of: performing melt spinning on a mixed solution obtained by mixing a Tween-modified copper nanoparticle suspension with a polyethylene solution; The melt spinning comprises extruding the mixed solution in a twin-screw extruder and then extruding the mixed solution in a single-screw extruder to obtain a polyethylene-copper nanoparticle composite material monofilament; The temperature of the single screw extruder is 250-270°C, and the stretch ratio is 7.0-9.0; The extrusion temperature of the twin-screw extruder is 200~300℃.
2. The use according to claim 1, characterized in that: The molecular weight of the high-density polyethylene is 3 to 6 million.
3. The use according to claim 1, characterized in that: The Tween includes any one of Tween 20, Tween 40, Tween 60 or Tween 80.
4. The use according to claim 1, characterized in that: The diameter of the single filament of the polyethylene-copper nanoparticle composite material is 0.1-0.3 mm.
5. The use according to claim 1, characterized in that: The mixing reaction of the Tween-modified copper nanoparticle suspension and the polyethylene solution includes stirring the reaction under the condition of heating in a water bath.
6. The use according to claim 5, characterized in that: The water bath heating temperature is 95-100°C.
7. The use according to claim 5, characterized in that: The stirring time is 0.5 to 2 hours.
8. The use according to claim 1, characterized in that: The preparation of the Tween-modified copper nanoparticle suspension comprises dispersing copper nanoparticles into a Tween alcohol solution and stirring; In the alcohol solution of Tween, the content of Tween is 0.1-1%; The stirring time is 3 to 10 minutes; The alcoholic solution of Tween is ethanol solution.
9. The use according to claim 1, characterized in that: The anti-pollution plastic product is a floating body of a water surface photovoltaic power station.
Citation Information
Patent Citations
Anti-bacterial film for agricultule
KR1020160011118A
Wrap film of multi layer
KR102229068B1